Feed type for induced molting of commercial layer hens - dos Santos, Graciene Conceição [UNESP]; Garcia, Edivaldo Antônio [UNESP]; Vieira Filho, Javer Alves [UNESP]; Molino, Andréa de Britto [UNESP]; Pelícia, Kleber; Berto, Daniella Aparecida [UNESP]; Floriano Murakami, Elise Saori [UNESP]; Montenegro, Andressa Takahara [UNESP] (FapUNIFESP (SciELO), 2014)
An experiment employing three hundred and twenty 81-week-old Lohmann LSL commercial-breed hens was conducted to compare alternative induced-molting methods with the conventional method (fasting). Induced molting lasted 28 days at most, production and quality being monitored for four periods of 28 days thereafter. A completely randomized experimental design with five treatments, eight replicates of eight birds each per plot was adopted. The following experimental treatments were applied until a loss of 26% of body weight was reached: T1-fasting, T2-wheat bran ad libitum, T3-rice bran ad libitum, T4-cracked rice ad libitum, T5-ground alfalfa ad libitum. Birds were then fed production diet ad libitum, except for those on treatment T1 (fasting) which received 30, 60 and 100 g/bird/day and then feed ad libitum. During induced molting the birds were exposed to a natural photoperiod and at day 28 that period was increased by 30 minutes/week until reaching 16 hours of light/day. The characteristics evaluated during induced molting were: feed intake, body weight changes and laying percentage. In the post-molt period, performance (feed intake, laying percentage, egg weight, egg mass, feed conversion ratio per dozen and per egg mass and percentage of broken eggs) and egg quality (specific gravity, eggshell breaking strength, percentages of eggshell, yolk, and albumen, eggshell thickness, yolk color and Haugh unit) were evaluated. Every 28 days one egg was collected from each repetition for three consecutive days for quality assessment. The use of rice bran and wheat bran is viable as molting inducers since the birds given those treatments display performance and egg quality similar to those fasted during the induced molting and also because these ingredients promote easier handling, eliminates the need for grinding and feed-mixing equipment and, being less aggressive, provide greater bird welfare. © 2014 Sociedade Brasileira de Zootecnia.
Keywords: Cracked rice; Egg production; Ground alfalfa; Rice bran; Wheat bran